Study Relation Between ?-fetoprotein with Repeated Abortion in Pregnant Women in the Iraqi Population - Hammadi, Amer A. (Scientific Journal of Medical Research, 2022)
Background: Alpha-fetoprotein was even a minor reason for the frequent abortion in the woman. Objective: The study aimed to know the relationship between Alpha-fetoprotein infection and women who suffer from repeated abortion. Methods: A sample from 115 women, in age between (20-05) years were enrolled in the current studies, and each patient and control blood samples were collected, and appreciation of IgG and IgM rate of Alpha-fetoprotein in serum of woman by ELISA technique was done. Results: By ELISA technique test, 7.8% Alpha-fetoprotein circulating level IgM and IgG antibody increasing showed results in the current study between the in woman's with repeated abortion history from total cases in three Iraqi cities. There is a relation between age and repeated abortion in most abortion cases in younger age between 15 to 45 years old and the abortion in pregnant women in the second period of gestation. The result shows there is no relation between abortion and area of life. Conclusion: Alpha-fetoprotein is an important reason of repeated abortion in women. Alpha-fetoprotein increasing detecting by technique would be done during pregnancy.